Halal Risk Mitigation And Food Safety In Herbal Medicine Producers Using FMEA And SWOT Methods - Nauval Abil Ikhsan, Muhammad; Catur Wahyuni, Hana (International Journal on Orange Technologies, 2025)
Halal suppy chain management is halal supply network that managed to ensure halal integrity from raw materials to end consumers. Halal and food safety are important for consumers to choose the food to be consumed. The purpose of this study (1) To determine the priority of halal supply chain and food safety using the FMEA method (2) To determine the strategy to improve the risk of halal supply chain and food safety using the SWOT method. In this study, the highest RPN value of 261 was obtained in the selection of kencur raw materials because the business bought kencur raw materials from collectors in traditional markets so they didn’t know the material was safe for consumption or not. In the SWOT method, the results are obtained at quadrant point I, which means that business has many strengths and opportunities, and very possible for businesses to develop and achieve maximum progress.